A link between the pressure dependency of elastic and electrical properties of porous rocks - Han, T.; Gurevich, Boris; Pervukhina, Marina; Clennell, M. (2016)
We present a technique to invert for the stiff and compliant porosity from velocity measurements made as a function of differential pressure on saturated sandstones. A dual porosity concept is used for dry rock compressibility and a squirt model is employed for the pressure and frequency dependent elastic properties of the rocks when saturated. The total porosity obtained from inversion shows satisfactory agreement with experimental results. The electrical cementation factor was determined using the inverted porosity in combination with measured electrical conductivity. It was found that cementation factor increased exponentially with increasing differential pressure during isostatic loading. Elastic compressibility, electrical cementation factor and electrical conductivity of the saturated rocks correlate linearly with compliant porosity, and electrical cementation factor and electrical conductivity exhibit linear correlations with elastic compressibility of the saturated rocks under loading. The results show that the dual porosity concept is sufficient to explain the pressure dependency of elastic, electrical and joint elastic-electrical properties of saturated porous sandstones.